Assessment of Delay Factors in Saudi Arabia Railway/Metro Construction Projects - Mohammed Gopang, Raja Khan; alias Imran, Qadir Bux; Nagapan, Sasitharan (International Journal of Sustainable Construction Engineering and Technology, 2020)
Railway construction industry has devoted vast amount of resources into advancing the management and technology of railway construction, yet most project in this industry often failed to comply with the set deadlines and budget limits. This study was conducted to recognize the critical factors that are causing delays in the construction of Riyadh Metro project, Saudi Arabia. From a thorough literature review, thirty-six (36) factors causing delays were identified which were then distributed to qualified industry experts in a survey questionnaire. A total of 105 respondents were gathered during the data collection. The data was then evaluated statistically by utilizing different calculation tools that are frequency adjusted importance index for the delay factor ranking, and Spearman’s correlation coefficient for the link between two different set of data. The result of this research identified the top five main delay factors to the railway construction projects which are â€œClient’s decision-making process and changes in control proceduresâ€, â€œDesign Errors (including ambiguities and discrepancies of details/specifications)â€, â€œLabor skills levelâ€, â€œDesign changes by Client or Consultantâ€ and lastly, â€œIssues regarding permissions/ approvals from other stakeholdersâ€. Finally, this study is hoped to help the railway construction industry in bettering itself by highlighting which issues should be focused on to counter the delays and reduce downtimes.